Biowaste Sago Bark Based Catalyst Free Carbon Nanospheres: Waste to Wealth Approach - Hegde, G. (American Chemical Society, 2015)
Catalyst-free carbon nanospheres were synthesized using simple one-step pyrolysis techniques where biowaste sago bark is used as a carbon precursor. Obtained carbon nanospheres showed a porous nature and revealed that more than 95 carbon is present in the synthesized carbon nanospheres with particle size ranging from 40 to 70 nm. An electrochemical study showed a specific capacitance value of 180 F g-1 at 2 mV s-1 and the cycling stability up to 1700 cycles. Obtained carbon nanospheres are useful in supercapacitor applications. The presented study revealed a waste to wealth approach thereby reducing waste in the environment. (Graph Presented). Â© 2015 American Chemical Society.